Endonasal Endoscopic Excision of Juvenile Nasopharyngeal Angiofibroma- The Technical Difficulties & Advantages - Biswas, Sudhangshu Shekhar; Amin, Zaheer Al; Amin, Zaheer Al; Chakrabortty, Rajashish; Chakrabortty, Rajashish; Mahbub, Shawhely; Mahbub, Shawhely; Halder, Soma; Halder, Soma (BIRDEM Medical Journal, 2014)
Objective: Endoscopic excision of juvenile nasopharyngeal angiofibroma (JNA) was carried out with the objective of minimizing blood loss and attempting to complete excision of tumor under direct vision with the help of Hopkins telescope. Study design: A retrospective 12 year study of 6 cases of JNA treated by endoscopic excision is presented. Result: According to Radkowskis classification, two patients were stage Ia, two were stage Ib and two patients were stage IIb. The mean duration of the surgery was 2 hours. The mean intra-operative blood loss was 575 ml. The mean follow up after the primary operation was 23.3 months. All the patients but one were free of disease. One patient had a recurrence in the pterygopalatine fossa requiring a successful revision procedure 3 years after the primary surgery. Conclusion: Endoscopic resection of JNA is a difficult but effective operation in experienced hands. The endoscopic management had less intra operative blood loss, lower occurrence of complications, shorter length of hospital stays and lower rate of recurrence. So it should be considered as a first choice option. Birdem Med J 2014; 4(2): 74-78